Assessment of the mode of action underlying development of rodent small intestinal tumors following oral exposure to hexavalent chromium and relevance to humans. (March 2013) - Thompson, Chad M.; Proctor, Deborah M.; Suh, Mina; Haws, Laurie C.; Kirman, Christopher R.; Harris, Mark A.
Abstract Chronic exposure to high concentrations of hexavalent chromium (Cr(VI)) in drinking water causes intestinal adenomas and carcinomas in mice, but not in rats. Cr(VI) causes damage to intestinal villi and crypt hyperplasia in mice after only one week of exposure. After two years of exposure, intestinal damage and crypt hyperplasia are evident in mice (but not rats), as are intestinal tumors. Although Cr(VI) has genotoxic properties, these findings suggest that intestinal tumors in mice arise as a result of chronic mucosal injury. To better understand the mode of action (MOA) of Cr(VI) in the intestine, a 90-day drinking water study was conducted to collect histological, biochemical, toxicogenomic and pharmacokinetic data in intestinal tissues. Using MOA analyses and human relevance frameworks proposed by national and international regulatory agencies, the weight of evidence supports a cytotoxic MOA with the following key events: (a) absorption of Cr(VI) from the intestinal lumen, (b) toxicity to intestinal villi, (c) crypt regenerative hyperplasia and (d) clonal expansion of mutations within the crypt stem cells, resulting in late onset tumorigenesis. This article summarizes the data supporting each key event in the MOA, as well as data that argue against a mutagenic MOA for Cr(VI)-induced intestinal tumors.